SURAT BERHARGA SEBAGAI ALAT LEGALITAS TRANSAKSI: STUDI TENTANG STRUKTUR DAN FUNGSINYA - Resika Triani Putri; Muchammad Galih Yuliansyah; Habib Rayodin; Norma Fitria (CV. KAMPUS AKADEMIK PUBLISING, 2024)
As a legitimate method of exchange, securities play a significant role in the commerce and economic sectors. The purpose of this study is to examine the composition and operation of securities in connection with their application as evidence of debt recognition or ownership. In order to understand the legal aspects of securities and their function in promoting transaction efficiency, a study was carried out on a variety of securities, including checks, money orders, bonds, stocks, demand deposits, and others. The study's findings demonstrate that securities serve as both legitimate proof and legal assurances for the parties concerned. Securities are therefore a crucial tool for establishing legal certainty and security in commercial operations.